RETROSPECTIVE ANALYSIS OF MATERNAL, NEONATAL AND EARLY-LIFE RISK FACTORS IN CHILDREN WITH INFLAMMATORY BOWEL DISEASE. - Yegembayeva, Nurgul (Nazarbayev University School of Medicine, 2024)
Background: IBD is believed to arise from genetic, environmental and geological aspects. Possibly related environmental factors extend from a child delivery mode and exposures in first year such as breastfeeding, antibiotic administration to late adulthood exposures as smoking, lifestyle, infections and diet. Methods: We have recruited 50 patients in each group: cases and controls.Cases consisted of children with IBD, while the control group included children who didn’t have a history of IBD or any autoimmune disease. The data is analyzed by logistic regression. Risk factors that could promote the IBD are the objective of this study. Results: Logistic analysis revealed that risk of developing of IBD is significantly associated height at birth (adjusted OR 1.79;95% CI:1.17 – 2.74,p<0.007), inversely associated with birth week (adjusted OR 0.33;95% CI:0.2 – 0.56,p<0.001) and formula feeding (adjusted OR 0.1; 95% CI:0.018 – 0.63, p=0.014). Conclusion: Our study revealed that the odds of developing IBD increases by 79% with an increase of height at birth by 1 cm, however the odds decrease by 69% as birth week increases by 1 week. Children which were fed with formula have substantially lower odds of developing IBD.
Keywords: type of access: gated access